LANGUAGE USE OF THE IBAN PEOPLE IN IBAN DOMINANT AND NON-IBAN DOMINANT AREAS IN SARAWAK - Lily, METOM; Ting, Su Hie; Ling, Hsin-Nie (2021)
The study examined the language use of the Iban people in Iban dominant and non-Iban dominant areas in Sarawak. Questionnaire data were obtained from 84 Iban respondents on their language use in nine domains. The findings showed that regardless of the numerical dominance of Iban in the area, almost all the Iban respondents spoke Iban with their family, but they mostly used Sarawak Malay Dialect in public places and the market. In Iban dominant areas, Iban is the main language of communication with neighbours, friends, classmates, and for prayers, while Sarawak Malay Dialect is mostly used with workmates. However, in the non-Iban dominant areas, Iban is mostly used only with neighbours but English is used mostly with classmates, workmates, and for prayers. The participants also used Sarawak Malay Dialect when interacting with their friends. As for social media communication, respondents from both Iban dominant and non-Iban dominant areas used mainly English. The exception is on writing SMS messages, where respondents from Iban dominant areas used mostly Iban. The study showed that in non-Iban dominant areas, the ethnic language is losing ground in communication with friends and classmates, and for praying, indicating that these are the domains that will see potential shift in future